Lelang Non Eksekusi oleh Pejabat Lelang Kelas 2 (Notaris) Dalam Peraturan Menteri Keuangan Republik Indonesia No. 122 Tahun 2023 tentang Petunjuk Pelaksanaan Lelang - Fatihatul Husna Maulida (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Auction is a mechanism for the open sale of goods with the highest price bidding system regulated in various regulations, including the Minister of Finance Regulation Number 122 of 2023 which updates auction governance in Indonesia. One important aspect of this regulation is the role of Class II Auction Officers, who are generally held by Notaries, in organizing voluntary non-execution auctions. This research uses a normative juridical method to analyze the role and authority of Class II Auction Officers in conducting auctions based on the latest regulations. The results show that Class II Auction Officers are responsible for leading the auction process, preparing minutes of the auction as an authentic deed, and ensuring legal certainty for the parties involved. In addition, the implementation of the electronic auction system presents new challenges related to technical aspects, legal validity, and transaction security. With these regulatory changes, the auction system in Indonesia is expected to become more efficient, transparent, and accountable in order to provide better legal protection for all stakeholders.